ANALISIS DAYA DUKUNG WISATA DAN PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN WISATA BAHARI PANTAI TORONIPA - Gerry Septian Nugraha; Anas Nikoyan; Muh. Ramli (Jurnal Perencanaan Wilayah, 2020)
The problems and objectives studied in the study were to analyze the effective carrying capacity of Eucalyptus Tourism (ECC) of Toronipa Beach according to landscape aspects, area and number of tourists; the form and level of community participation in the development of Toronipa Beach marine tourism; and the development of Toronipa Beach marine tourism to advance tourism and be more valuable and competitive. This study uses a quantitative and qualitative approach using survey design. The sample in the study were 27 people purposively. Data were analyzed quantiatively and descriptively quality. The results of the study concluded that the tourism carrying capacity (ECC) of Toronipa Beach was 25,592 people per day, or around 8,531 people every 3 hours. Community participation in the development of Toronipa Beach marine tourism is "quite high". The forms of community participation in the development of the Toronipa Beach marine tourism are;(a) Establish projects that are self-sufficient and funded entirely by the community; (b) Donations in the form of work (energy) include activities;(c) Consultation, socialization related to tourism development (usually in the form of services / honorariums) by participating in the socialization of marine tourism development organized by the government or non-government;(d) Mass actions (clean action, environmental management, safety and conservation of coastal biota); (e) Spontaneous contributions in the form of (money, goods and information) for tourism development purposes; and (f) Establishing self-supporting projects and donors coming from donations of individuals / institutions that are outside a certain environment. The effort to develop maritime tourism in Toronipa Beach is carried out through four (4) approaches, namely promotion, improvement of tourism quality (landscape), improvement of tourism services and human resources.Keywords: Toronipa Beach, Carrying Capacity and Participation